Analysis, modeling and simulations of an innovative sliding vane rotary compressor with a rotating cylinder. (15th February 2021) - Gu, Huaduo; Zhou, Xiaoyu; Chen, Yaping; Wu, Jiafeng; Wu, Zan; Jiang, Yunhui; Sundén, Bengt
Highlights: A new sliding vane compressor with a rotating cylinder is proposed and modeled. The friction losses at vane tips and between rotor and cylinder are reduced greatly. Flow fields show that the short length is preferable for the novel structure. Outlet temperature rises and flow rate declines with increasing pressure ratio εp . Under εp  = 5, volumetric efficiency and isentropic efficiency are 97.14% and 90.33%. Abstract: A novel sliding vane rotary compressor with a rotating cylinder is proposed in this paper. The sliding vane dynamics analysis reveals that, compared with the traditional compressor, the friction loss at the sliding vane tips and between rotor and cylinder can be reduced to 0.25% and 10.23%. To numerically investigate the internal flow mechanism, a reliable three-dimensional simulation method is developed via Fluent 2020R1. Three pressure ratios are considered. During transient calculations, all parameters begin to fluctuate periodically after the fourth round. Both temperature and pressure for a single chamber reach the maximum near the exhaust port. As the pressure ratio ε p increases from 5, 10 to 15, the outlet temperature increases from 496.9, 623.0 to 754.4 K and the mass flow rate decreases from 0.03089, 0.02946 to 0.02764 kg/s, the volumetric efficiency and isentropic compression efficiency decrease, with the maximum values of 97.14% and 90.33%. The gaps between the rotor and the cylinder and at the vane tips are 0.03 and 0.01 mm, but the leakage mass of the former is one order higher than that of the latter. The research can provide guidance for the design and practical application of sliding vane rotary compressors.